Bank privatization and performance: Empirical evidence from Nigeria - Beck, Thorsten; Cull, Robert; Jerome, Afeikhena (Journal of Banking & Finance, 2005)
We assess the effect of privatization on performance in a panel of Nigerian banks for the period 1990–2001. We find evidence of performance improvement in nine banks that were privatized, which is remarkable given the inhospitable environment for true financial intermediation. Our results also suggest negative effects of the continuing minority government ownership on the performance of many Nigerian banks. Finally, our results complement aggregate indications of decreasing financial intermediation over the 1990s; banks that focused on investment in government bonds and non-lending activities enjoyed a relatively better performance.